Co-infection of Fusarium aglaonematis sp. nov. and Fusarium elaeidis Causing Stem Rot in Aglaonema modestum in China - Zhang, Yunxia; Chen, Chao; Mai, Zhanglong; Lin, Jieying; Nie, Liting; Maharachchikumbura, Sajeewa S. N.; You, Chunping; Xiang, Meimei; Hyde, Kevin D.; Manawasinghe, Ishara S. (Frontiers in Microbiology, 2022)
Aglaonema modestum (Araceae) is an evergreen herbage which is intensively grown as an ornamental plant in South China. A new disease was observed in A. modestum from 2020 to 2021 in Guangdong province, China. The disease symptoms associated with plants were initial leaf wilt, stem rot and resulting plant death while leading to severe economic losses. In total, six Fusarium isolates were obtained from diseased plants. The putative pathogen was identified using both morphological characteristics and molecular phylogenetic analysis of calmodulin (cmdA), RNA polymerase largest subunit (rpb1), RNA polymerase II (rpb2), translation elongation factor-1α (tef 1-α) and beta-tubulin (β-tubulin) sequences. Two Fusarium species were identified, including one new species; F. aglaonematis belonging to F. fujikuroi species complex. In addition, F. elaeidis belonging to the F. oxysporum species complex was also identified. Pathogenicity assays were conducted by inoculating each species into potted A. modestum plants as well as co-inoculating two species. The results showed that two Fusarium species could infect plants independently as well as can infect together. Co-infection of these two species enhanced the disease severity of A. modestum. Compared to single inoculation of F. elaeidis, severity was higher and disease development was quicker when plants were inoculated with F. aglaonematis only. In addition, these two Fusarium species could infect Aglaonema plants without wounds, while inoculation with a physical injury increased disease severity. This is the first report of co-infection by F. aglaonematis and F. elaeidis causing stem rot on A. modestum worldwide. Our study will be an addition to the knowledge of Fusarium diseases in ornamental plants. These results will provide a baseline to identify and control diseases associated with A. modestum.